Expression Levels of Sperm Genes Associated with Energy Production Pathways Regulate Fertility Status of Bulls - Ramya, Laxman; Swathi, Divakar; Archana, Santhanahalli Siddalingappa; Arangasamy, Arunachalam; Binsila, B Krishnan; Krishnappa, Balaganur; Selvaraju, Sellappan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Sperm biomolecules impact the reproductive success of a bull in many ways from fertilization to the health of the offspring. The energy produced within the sperm enables them to remain motile and allows them to participate in fertilization events. In this study, we deciphered the genes associated with energy production and their influence on the fertility rate. Post-thaw buffalo semen samples (n=21) were analysed for sperm kinematics and field fertility for selecting high (n=5) and low (n=5) fertile samples. Sperm total RNAs were extracted using a double lysis method followed by column-based extraction and sequenced using the Illumina platform. The expression levels of the genes involved in energy-regulating pathways were analyzed. Among these genes, 14.6% were significantly (p<0.05) differentially expressed between high and low fertile sperm. The expression levels of up-regulated genes such as JAK3, DDX5, PRKCZ, CHD4, CHD5, and ADCY3 had a strong positive correlation (r>0.5) with progressive motility and velocities. In these, up-regulated genes were involved in chemokine signaling (ADCY2 and JAK2, p=0.0001), calcium signaling (AGTR1 and SLC25A4,p=0.0002) and oocyte meiosis (ADCY2 and ADCY3, p=0.049). The increase in the expression of ATP-producing genes substantiates the improved progressive motility (64.51±5.79 vs 33.07±3.34 %), curvilinear velocity (70.58±4.32 vs 50.15±4.92 μm/sec), straight-line velocity (39.84±3.16 vs 26.02±2.52 μm/sec) and average path velocity (49.46±3.59 vs 32.99±3.45 μm/sec) in high fertile bulls compared to low fertile bulls. The study suggests that the expression level of differentially expressed genes associated with energy-regulating pathways influences the fertilizing ability of sperm.